Establishing Organized Stroke Care in Low- and Middle-Income Countries: From Training of Non-specialist to Implementation - Sebastian, Ivy Anne; Demers, Marika; Yeghiazaryan, Nune; Asyraf WZ, Wan; Nasreldein, Ahmed; Gopaul, Urvashy; Charalambous, Marina; Thilarajah, Shamala; Khim, Kwah Li; Y Vishnu, Venugopalan (My University, 2023)
Low- and middle-income countries (LMICs) suffer from a higher stroke burden compared to high-income countries with higher mortality and disability due to stroke. However, the availability of resources, both infrastructural and personnel, is widely discrepant. The lack of specialist neurologists or stroke physicians in LMICs makes it imperative to rely on alternative models of stroke care. Task-sharing models such as the physician-led model or the non-specialist model have been evaluated previously with evidence for feasibility and cost-effectiveness. We propose to implement and assess the effectiveness of a non-specialist model of stroke care across 3 LMICs through a structured capacity building program, augmented by a tailored mobile application to guide the non-specialists in delivering optimal stroke care. This study will provide essential information on the effectiveness of a non-specialist driven delivery of stroke care on a larger scale across different regional contexts.
Keywords: Non-specialist stroke care; Physician-led stroke care; Alternative stroke care models; Telestroke